The Indonesian Government and Palestinian Refugees: Policy Responses and Humanitarian Support (Palestine Issues on Indonesian Society, 2024)
This paper investigates Indonesia’s policies on Palestinian refugees, focusing on the country’s humanitarian responses and its legal framework for offering asylum. Indonesia has historically demonstrated strong solidarity with Palestine, but its policies toward Palestinian refugees are complex and multifaceted. The study examines Indonesia’s stance on the issue within the broader context of its immigration policies, international refugee conventions, and bilateral relations with Palestinian authorities. It also analyzes the support provided by non-governmental organizations (NGOs) in Indonesia, as well as the legal challenges refugees face in terms of residency, employment, and access to services. By assessing Indonesia’s role in the international refugee system and its approach to Palestinian refugees, this paper highlights the tension between Indonesia’s commitment to human rights and the practical limitations of its domestic legal frameworks. It concludes by considering the role of Indonesia in influencing regional and global discourse on refugee rights, particularly in the context of the Palestinian crisis.